1x-2=3x+2-6xx2-4

Rewrite 4 as 22.

1x-2=3x+2-6xx2-22

Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=x and b=2.

1x-2=3x+2-6x(x+2)(x-2)

1x-2=3x+2-6x(x+2)(x-2)

Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.

x-2,x+2,(x+2)(x-2)

The LCM is the smallest positive number that all of the numbers divide into evenly.

1. List the prime factors of each number.

2. Multiply each factor the greatest number of times it occurs in either number.

The number 1 is not a prime number because it only has one positive factor, which is itself.

Not prime

The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.

1

The factor for x-2 is x-2 itself.

(x-2)=x-2

(x-2) occurs 1 time.

The factor for x+2 is x+2 itself.

(x+2)=x+2

(x+2) occurs 1 time.

The factor for x-2 is x-2 itself.

(x-2)=x-2

(x-2) occurs 1 time.

The LCM of x-2,x+2,x+2,x-2 is the result of multiplying all factors the greatest number of times they occur in either term.

(x-2)(x+2)

(x-2)(x+2)

Multiply each term in 1x-2=3x+2-6x(x+2)(x-2) by (x-2)(x+2) in order to remove all the denominators from the equation.

1x-2⋅((x-2)(x+2))=3x+2⋅((x-2)(x+2))-6x(x+2)(x-2)⋅((x-2)(x+2))

Cancel the common factor of x-2.

Cancel the common factor.

1x-2⋅((x-2)(x+2))=3x+2⋅((x-2)(x+2))-6x(x+2)(x-2)⋅((x-2)(x+2))

Rewrite the expression.

x+2=3x+2⋅((x-2)(x+2))-6x(x+2)(x-2)⋅((x-2)(x+2))

x+2=3x+2⋅((x-2)(x+2))-6x(x+2)(x-2)⋅((x-2)(x+2))

Simplify 3x+2⋅((x-2)(x+2))-6x(x+2)(x-2)⋅((x-2)(x+2)).

Simplify each term.

Cancel the common factor of x+2.

Factor x+2 out of (x-2)(x+2).

x+2=3x+2⋅((x+2)(x-2))-6x(x+2)(x-2)⋅((x-2)(x+2))

Cancel the common factor.

x+2=3x+2⋅((x+2)(x-2))-6x(x+2)(x-2)⋅((x-2)(x+2))

Rewrite the expression.

x+2=3⋅(x-2)-6x(x+2)(x-2)⋅((x-2)(x+2))

x+2=3⋅(x-2)-6x(x+2)(x-2)⋅((x-2)(x+2))

Apply the distributive property.

x+2=3x+3⋅-2-6x(x+2)(x-2)⋅((x-2)(x+2))

Multiply 3 by -2.

x+2=3x-6-6x(x+2)(x-2)⋅((x-2)(x+2))

Cancel the common factor of (x-2)(x+2).

Move the leading negative in -6x(x+2)(x-2) into the numerator.

x+2=3x-6+-6x(x+2)(x-2)⋅((x-2)(x+2))

Factor (x-2)(x+2) out of (x+2)(x-2).

x+2=3x-6+-6x(x-2)(x+2)(1)⋅((x-2)(x+2))

Cancel the common factor.

x+2=3x-6+-6x(x-2)(x+2)⋅1⋅((x-2)(x+2))

Rewrite the expression.

x+2=3x-6-6x

x+2=3x-6-6x

x+2=3x-6-6x

Subtract 6x from 3x.

x+2=-3x-6

x+2=-3x-6

x+2=-3x-6

Move all terms containing x to the left side of the equation.

Add 3x to both sides of the equation.

x+2+3x=-6

Add x and 3x.

4x+2=-6

4x+2=-6

Move all terms not containing x to the right side of the equation.

Subtract 2 from both sides of the equation.

4x=-6-2

Subtract 2 from -6.

4x=-8

4x=-8

Divide each term by 4 and simplify.

Divide each term in 4x=-8 by 4.

4×4=-84

Cancel the common factor of 4.

Cancel the common factor.

4×4=-84

Divide x by 1.

x=-84

x=-84

Divide -8 by 4.

x=-2

x=-2

x=-2

Exclude the solutions that do not make 1x-2=3x+2-6xx2-4 true.

No solution

Solve for x 1/(x-2)=3/(x+2)-(6x)/(x^2-4)